2016
DOI: 10.1089/jop.2015.0163
|View full text |Cite
|
Sign up to set email alerts
|

Automated Measurement of Cobblestone Morphology for Characterizing Stem Cell Derived Retinal Pigment Epithelial Cell Cultures

Abstract: Purpose: Assessing the morphologic properties of cells in microscopy images is an important task to evaluate cell health, identity, and purity. Typically, subjective visual assessments are accomplished by an experienced researcher. This subjective human step makes transfer of the evaluation process from the laboratory to the cell manufacturing facility difficult and time consuming. Methods: Automated image analysis can provide rapid, objective measurements of cultured cells, greatly aiding manufacturing, regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…We profiled differentiation of one research and two clinical grade cell lines (HS980, KARO1, and E1C3, respectively) at six time points (day 7 [D7], D14, D30, D38, D45, and D60; Table S1 ). Morphological evaluation using cobblestone junction scores confirmed that changes in cell shape and size followed differentiation as cells progressively assumed a tighter cobblestone monolayer of pigmented cells ( Joshi et al., 2016 ) ( Figures 1 B, S1 A, and S1B).
Figure 1 Global scRNA-seq characterization of hESC-RPE differentiation trajectory (A) Schematic of the hESC-RPE differentiation experimental protocol where scRNA-seq was performed at the seven time points (bolded; D, day) in three cell lines: HS980, KARO1, and E1C3.
…”
Section: Resultsmentioning
confidence: 76%
“…We profiled differentiation of one research and two clinical grade cell lines (HS980, KARO1, and E1C3, respectively) at six time points (day 7 [D7], D14, D30, D38, D45, and D60; Table S1 ). Morphological evaluation using cobblestone junction scores confirmed that changes in cell shape and size followed differentiation as cells progressively assumed a tighter cobblestone monolayer of pigmented cells ( Joshi et al., 2016 ) ( Figures 1 B, S1 A, and S1B).
Figure 1 Global scRNA-seq characterization of hESC-RPE differentiation trajectory (A) Schematic of the hESC-RPE differentiation experimental protocol where scRNA-seq was performed at the seven time points (bolded; D, day) in three cell lines: HS980, KARO1, and E1C3.
…”
Section: Resultsmentioning
confidence: 76%
“…Rather than using a combination of simple pairwise information distances (NGD's), the spectral approach [26] constructs a representation of the objects being clustered using an eigen decomposition. In previous work, we have found such spectral approaches to be most accurate when working with compression-based distance measures [7,8,12]. Mapping from clusters to classes for the pairwise analysis is done following the spectral clustering step by using a majority vote.…”
Section: Methodsmentioning
confidence: 99%
“…Consider a different example, where ML is applied to whole images. Joshi and colleagues categorised images of cultured stem cells as they differentiate into retinal pigment epithelium 46 . Automated categorisation of cultures according to the maturation level has applications in stem cell replacement therapy for conditions associated with loss of retinal pigment epithelium.…”
Section: Implicit Data Representationmentioning
confidence: 99%
“…Joshi and colleagues categorised images of cultured stem cells as they differentiate into retinal pigment epithelium. 46 Automated categorisation of cultures according to the maturation level has Normalised compression distance 46 Normalised compression distance; 47 support vector machines 37 Unsupervised learning Instances without labels Non-negative matrix factorisation 13 Otsu thresholding 36 viSNE 53 Probabilistic graphical models 55 AL Interactively request labels AL for improving cell tracking 49 AL strategies for high-content screening 51…”
Section: Data Representation and Deep Learningmentioning
confidence: 99%